Dendritic spine and synapse pathology in chromatin modifier-associated autism spectrum disorders and intellectual disability - Ford, Thomas James L.; Jeon, Byeong Tak; Lee, Hyunkyoung; Kim, Woo-Yang (Frontiers in Molecular Neuroscience, 2023)
Formation of dendritic spine and synapse is an essential final step of brain wiring to establish functional communication in the developing brain. Recent findings have displayed altered dendritic spine and synapse morphogenesis, plasticity, and related molecular mechanisms in animal models and postmortem human brains of autism spectrum disorders (ASD) and intellectual disability (ID). Many genes and proteins are shown to be associated with spines and synapse development, and therefore neurodevelopmental disorders. In this review, however, particular attention will be given to chromatin modifiers such as ARID1B, KANSL1, and WDR5 which are among strong susceptibility factors for ASD and ID. Emerging evidence highlights the critical status of these chromatin remodeling molecules in dendritic spine morphogenesis and synaptic functions. Molecular and cellular insights of ARID1B, KANSL1, and WDR5 will integrate into our current knowledge in understanding and interpreting the pathogenesis of ASD and ID. Modulation of their activities or levels may be an option for potential therapeutic treatment strategies for these neurodevelopmental conditions.